The Status of the Human Soul Between the Distinctness from the Body (Mugayeret ) and the Abstractness from the Body (Tajarrud ): The Case of Ali Qushji - M. Zahit Tiryaki (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The nature of the soul and its relationship to the body has been a subject of debate throughout history. In ancient Hellenistic times and the Middle Ages, the discussion revolved around whether the soul could be reduced to the body and bodily elements. This debate evolved into a consideration of whether the mind could be reduced to the body in the modern and contemporary periods. This ongoing debate can be observed in the classical and post-classical periods of Islamic philosophy and theology. Islamic philosophers largely upheld substance dualism, distinguishing the soul as an immaterial and incorporeal abstracted substance, and the body as a material and corporeal concrete substance. They argued for the distinctness of the soul and the body, presenting the soul as an abstracted substance. However, some theologians, particularly in the post-classical period, agreed on the distinctness of the soul from the body but diverged from the philosophers on the abstractness of the soul from the body. They criticized the philosophical proofs that the soul is an abstracted substance. Ali Qūshjī played a significant role in this debate by emphasizing the soul’s distinction from the body and challenging the arguments for the soul being an abstracted substance. This study aims to analyze the difference between the distinctness of the soul from the body and the abstractness of the soul from the body through the example of Ali Qūshjī. It seeks to determine Ali Qūshjī’s position in this enduring debate, which has spanned from the ancient Hellenistic period to the modern and contemporary period.